Fikih Media Sosial sebagai Landasan Etika Komunikasi On-Line - Siti Khoirotul Ula (Proceedings of Annual Conference for Muslim Scholars, 2017)
The existence of social media moves the interpersonal interaction communication from reallity to virtual communication. Indirect interaction has positive and negative impact. Disputes arising on social media have caused chaos on reality. However, as a public entity, Muslim can’t be separated from this era, including using social media. Discourse Fiqh of Social Media be attended by Moslems, although its rared. Fiqh of Social Media is the new terminology that has’t been discussed at classical fiqh. The Aims of this article to explane of fiqh relevances to be ethical codes at online communication. Based on the argument of al-Qur’an and Hadith, there are three rules that must be understood by user of social media at reinformating the information obtained from social media. There are: First, know the validity of the news. Second, informing the helpful news. Third, consider the maslahat aspect of the news, even the news is true.Keyword : fiqh of social media, ethics, online communication